Innovating Learning Models: The Impact of Tabata and Rubber Weight on Tapak Suci Kick Speed - Nasrawati Nasrawati; Imam Suyudi; Sudirman Sudirman (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Lack of variation in physical training models often leads to performance stagnation, particularly in straight kick speed—a critical technique in Pencak Silat. This study explores innovating learning models to overcome these limitations. This research aims to analyze the impact of Tabata training and rubber weight innovations on increasing the straight kick speed of Tapak Suci Putera Muhammadiyah (PIMDA) 181 students’ athletes in Majene Regency. This experimental study utilized two group pretest-posttest designs with a sample of 30 students, selected based on active training and achievement criteria. Data were collected using a 10-second straight kick speed test and analyzed via descriptive, normality, homogeneity, and t-tests. The findings demonstrate a significant effect from the Tabata training model (t_count 4.993 > t_table 2.145; sig. 0.000 < 0.05). Similarly, the rubber weight training model showed a substantial impact with a t_count of 9.808. Integrating these innovative learning models provides a practical contribution for coaches and educators to optimize motor skills and athlete performance within martial arts environments.